LEGAL ANALYSIS OF THE KPPA AGREEMENT BETWEEN THE COMMUNITIES OF THE VILLAGES OF TAMBUSAI TIMUR, TINGKOK, AND LUBUK SOTING AND PT. HUTAHAEAN - Siti Rahma; Almadison; Dani Kurniawansyah; Riski Anla Pater; Putri Habibah Siregar (RADJA PUBLIKA, 2025)
This study analyzes the plasma partnership agreement (KKPA) between the communities of East Tambusai, Tingkok, and Lubuk Soting villages and PT Hutahaean, which has been in place since 1999. The agreement stipulates a 65% profit sharing agreement for the community and 35% for the company. However, the community claims that their rights have not been fulfilled, particularly regarding the reallocation of the 20% plasma, unpaid profit sharing, and land use outside the company's HGU (land use permit). Using a qualitative approach, this study collected data from agreement documents, field identification results, and interviews with community leaders and relevant officials. The results indicate that PT Hutahaean has occupied community land without valid permits and has not fulfilled its obligations in accordance with applicable laws and regulations. Based on these findings, this study recommends: (1) law enforcement against PT Hutahaean for breach of contract and unauthorized land use; (2) the formation of an integrated team involving the government, the Regional People's Representative Council (DPRD), and indigenous communities to resolve the dispute; (3) reviewing the company's HGU status and evaluating the feasibility of its extension; and (4) delaying plasma reallocation and profit sharing payments. This research is expected to contribute to the resolution of agrarian disputes and become a reference for fairer and more sustainable natural resource management policies.